Determinants of Glycosaminoglycan (GAG) Structure - Kristian Prydz (Biomolecules, 2015)
Proteoglycans (PGs) are glycosylated proteins of biological importance at cell surfaces, in the extracellular matrix, and in the circulation. PGs are produced and modified by glycosaminoglycan (GAG) chains in the secretory pathway of animal cells. The most common GAG attachment site is a serine residue followed by a glycine (-ser-gly-), from which a linker tetrasaccharide extends and may continue as a heparan sulfate, a heparin, a chondroitin sulfate, or a dermatan sulfate GAG chain. Which type of GAG chain becomes attached to the linker tetrasaccharide is influenced by the structure of the protein core, modifications occurring to the linker tetrasaccharide itself, and the biochemical environment of the Golgi apparatus, where GAG polymerization and modification by sulfation and epimerization take place. The same cell type may produce different GAG chains that vary, depending on the extent of epimerization and sulfation. However, it is not known to what extent these differences are caused by compartmental segregation of protein cores en route through the secretory pathway or by differential recruitment of modifying enzymes during synthesis of different PGs. The topic of this review is how different aspects of protein structure, cellular biochemistry, and compartmentalization may influence GAG synthesis.